Formação de leitores literários: parâmetros curriculares e práticas docentes - (:unkn) unknown (Universidade Federal do Pampa, 2012)
The Language an Arts undergraduate program made clear that many aspects related to the teaching of Portuguese are not always easily applicable in to the daily school practice an enunciative perspective, allows us to see the work with the language of primary importance in the citizenship formation. The formation of literary readers is one of the things that stood out to me. Since the PCNS, National Curriculum, were prepared to assist and guide teaching practices it instigated a question: "What is the relation between teachers and official documents (PCNS), specifically with respect to the formation of literary readers?" Therefore, this paper proposes the study of what is the relation established by teachers working at city of Bage Primaria / RS, with the views of teaching Portuguese language present at PCNS, specially the ones concerning the work of literary readers formation. For this analysis, we first made a historical background on curriculum development in general and specifically in Brazil, portraying a historical glimpse of Portuguese language discipline in this country. Second, we analyzed the teaching of language as it appears in the concepts of PCNS and connected to the concepts studied in the formation of literary readers. After that we investigated the questionnaires responses using the evidentiary paradigm of Ginzburg, as this process takes place in the practice of teachers in classroom. Finally, we made a comparative analysis about similarities and differences occurring on theory and practice.
Keywords: Letras; Parâmetros Curriculares Nacionais (PCNs); Língua portuguesa; Literatura; Letramento literário; Letters; National Curriculum (PCN); Portuguese language; Literature; Literary literacy; CNPQ::LINGUISTICA, LETRAS E ARTES